2010
DOI: 10.1017/s0144686x10000863
|View full text |Cite
|
Sign up to set email alerts
|

‘If I look old, I will be treated old’: hair and later-life image dilemmas

Abstract: This paper considers the social symbolism of hair, how it is managed and styled in later life, and what attitudes to appearance in general and hairstyling in particular reveal about ageism in contemporary culture. The paper draws on findings from a two-year, nationwide, participative study of age discrimination in the United Kingdom, the Research on Age Discrimination (RoAD) project. Using data collected by qualitative methods, including participant diaries and interviews undertaken by older field-workers, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 41 publications
(40 reference statements)
4
41
0
Order By: Relevance
“…This is also supported by other researchers that have found that the media perpetuates harmful stereotypes and promotes negative attitudes toward the elderly [4] [19]. There appears to be a fear of aging in society that causes people to experience a sense of negativity toward the elderly and a general sense of anxiety about getting older [6].…”
Section: Literature Reviewsupporting
confidence: 65%
See 1 more Smart Citation
“…This is also supported by other researchers that have found that the media perpetuates harmful stereotypes and promotes negative attitudes toward the elderly [4] [19]. There appears to be a fear of aging in society that causes people to experience a sense of negativity toward the elderly and a general sense of anxiety about getting older [6].…”
Section: Literature Reviewsupporting
confidence: 65%
“…They explained this through a larger historical perspective that looked at issues with cultural tolerance, industrialization, conflict over resources, and overall contact (the contact hypothesis) and found that although Western societies also hold mixed attitudes toward their elderly members, those in the East seem to have a more negative disposition toward their elderly members [21]. This last point is interesting because there appears to be a strong feeling that older males are viewed more favorably than older females (e.g., less dependent, more autonomous, more competent, mores self-reliant), and women appear to be viewed as less attractive, less productive, and less intelligent [19] [20] [21]. It is widely believed that traditional belief systems and contemporary media play into these negative and harmful beliefs.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Similarly, we suggest that the mutual recognition and supportiveness displayed by salon clients, often facilitated by the hairdresser, can be understood as a response not only to the social isolation experienced/imposed within care settings but as resistance to the broader imposition of social invisibility upon older women (Ward and Holland 2011;Hurd-Clarke and Korotchenko 2010). In this respect our findings echo those of Furman…”
Section: Integrating An Intersectional Approachsupporting
confidence: 75%
“…In undertaking their various appearance practices older women face a number of challenges. Prime among these is managing to ‘grow old gracefully’ – striking the balance between doing too little or too much for their appearance (Furman 1997: 116; Hurd Clarke, Griffin and Maliha 2009; Jankowski et al 2016; Ward and Holland 2011). Women who do too little, particularly if they have the means at their disposal to take action, may at best meet with disapprobation for having ‘let themselves go’ (Brooks 2010; Coupland 2009), or at worst, find they are treated as invisible (Bytheway et al 2007: 31).…”
Section: Hair Ageing and Dilemmas Of Self-presentationmentioning
confidence: 99%